Gender-specific long-term results after elective open abdominal aortic aneurysm repair depending on the site of distal anastomosis - Annunziata, Sonny Gennaro; Epple, Jasmin; Schmitz-Rixen, Thomas; Böckler, Dittmar; Grundmann, Reinhart T. (Vascular and endovascular surgery, 2024)
Objective - Analysis of gender-specific differences in short- and long-term outcome after elective open abdominal aortic aneurysm repair (OAR) regarding the distal anastomosis. - Methods - In this retrospective cohort study, data from 4853 patients of a German health insurance company undergoing OAR for infrarenal abdominal aortic aneurysms (AAAs) between 2010 and 2016 were analysed. The patients were followed through 2018. - Results - A total of 4050 (83.5%) men and 803 (16.6%) women underwent OAR. Women were older than men (72.9 ± 8.7 vs 69.8 ± 8.5 years; P < .001). A tube graft was used in 2644 (54.5%) patients, an aorto-biiliac bifurcated graft in 1657 (34.1%) and an aorto-bifemoral bifurcated graft in 552 (11.4%). Perioperative mortality was not significantly different between men (5.7%) and women (6.5%) in the total patient population (P = .411). This was true for aorto-aortic tube grafting (P = .361), aorto-biiliac reconstructions (P = 1.000) and aorto-bifemoral reconstructions (P = .345). Kaplan-Meier estimated long-term survival of men after 9 years was better than that of women (55.0% vs 43.8%; P = .006). However, separated by the site of the distal anastomosis, this was only true for aorto-aortic reconstructions (survival men vs women 56.0% vs 42.1%; P = .005), not for aorto-biiliac and aorto-bifemoral reconstructions. In the multivariate Cox regression analysis, age over 80 years, heart failure, aorto-bifemoral reconstruction, chronic kidney disease stage 3-5, chronic obstructive pulmonary disease, peripheral artery disease, arterial hypertension, but not gender (P = .531), had a negative impact on long-term survival. - Conclusion - If possible, an aorto-aortic tube graft should be preferred to aorto-biiliac and aorto-bifemoral reconstructions in OAR. Patients selected for aorto-bifemoral artery reconstruction exhibit higher perioperative morbidity and mortality as well as worse long-term survival compared to patients selected for an intra-abdominal reconstruction. In the multivariate regression analysis, gender was not an independent risk factor for either short- or long-term outcomes.